PENGEMBANGAN VIDEO EDUALRT SEBAGAI MEDIA PENYULUHAN KESELAMATAN BERKENDARA BAGI PENGEMUDI BUS - Dimas Nugroho Putro; Dani Fitria Brilianti; Sugianto Sugianto (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2025)
Traffic accidents involving route buses remain a serious issue in the transport sector. One of the main causes is the low level of understanding among drivers of the principles of safe driving. This research project aims to design and develop educational media in the form of e-learning videos to counsel bus drivers at the Sudiro Tungga Jaya Bus Company on safe driving practices. The Research and Development (R&D) method was employed, using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The videos cover fatigue management, road hazard management and travel management plans. The material and media were validated by experts and the effectiveness was evaluated through a pre-test and post-test with 40 AKAP and AKDP bus drivers. The results showed that the educational video is a feasible and effective counselling tool, significantly increasing drivers' understanding of safe driving practices. The educational video proved to be attention-grabbing, easy to understand and effective in increasing participant involvement in the counselling seminar.